Репрезентація гендерних стереотипів у художній літературі = Representation of gender stereotypes in artistic literature - Dushko, Xrystyna; Maslova, Yuliya; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Dushko Xrystyna, Maslova Yuliya, Zukow Walery. Репрезентація гендерних стереотипів у художній літературі = Representation of gender stereotypes in artistic literature. Journal of Education, Health and Sport. 2016;6(5):329-340. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.53127 http://ojs.ukw.edu.pl/index.php/johs/article/view/3533 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. РЕПРЕЗЕНТАЦІЯ ГЕНДЕРНИХ СТЕРЕОТИПІВ У ХУДОЖНІЙ ЛІТЕРАТУРІ Representation of gender stereotypes in artistic literaturę Душко Христина Ігорівна Dushko Xrystyna Ihorivna Національний університет «Острозька академія» National University „Ostrog Academy” Маслова Юлія Петрівна Maslova Yuliya Petrivna Національний університет «Острозька академія» National University „Ostrog Academy” Zukow Walery Zukow Walery UMK w Toruniu UMK in Torun Анотація. У статті розглянуто поняття «гендерний стереотип» як феномен суспільства, а також проаналізовано особливості його створення та нівелювання у творах художньої літератури. Ключові слова: гендерні ролі, гендерний стереотип, фемінність, маскуліннсть, художня література, гендерлект. Аннотация. В статье рассмотрено понятие «гендерный стереотип» как феномен общества, а также проанализированы особенности его создания и нивелирования в произведениях художественной литературы. Ключевые слова: гендерные роли, гендерный стереотип, феминность, маскулиннсть, художественная литература, гендерлект. Summary. The article discusses the concept of “gender stereotype" as a phenomenon of society, and especially the creation and avoiding gender stereotypes in works of fiction literature. Key words: gender roles, gender stereotypes, femininity, maskulinity, fiction literature, henderlekt.